2018
DOI: 10.3390/ijms19123762
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Localization, and Activity of the Aryl Hydrocarbon Receptor in the Human Placenta

Abstract: The human placenta is an organ between the blood of the mother and the fetus, which is essential for fetal development. It also plays a role as a selective barrier against environmental pollutants that may bypass epithelial barriers and reach the placenta, with implications for the outcome of pregnancy. The aryl hydrocarbon receptor (AhR) is one of the most important environmental-sensor transcription factors and mediates the metabolism of a wide variety of xenobiotics. Nevertheless, the identification of diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…However, later in gestation, the fetus gains the capability of 5-HT synthesis (Arevalo et al, 1991;Sano et al, 2016). With increased IDO expression/activity at term, also reported before (Blaschitz et al, 2011;Murthi et al, 2017;Wakx et al, 2018), it seems plausible that at later stages of gestation, TRP is preferentially utilized for KYN production.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, later in gestation, the fetus gains the capability of 5-HT synthesis (Arevalo et al, 1991;Sano et al, 2016). With increased IDO expression/activity at term, also reported before (Blaschitz et al, 2011;Murthi et al, 2017;Wakx et al, 2018), it seems plausible that at later stages of gestation, TRP is preferentially utilized for KYN production.…”
Section: Discussionmentioning
confidence: 85%
“…In the placenta, this pathway plays a crucial role in preventing fetal rejection by the maternal immune system (Munn et al, 1998). Extensive studies have been carried out to evaluate IDO1 expression/localization in the placenta, indicating that IDO1 expression/function increases during gestation (Sedlmayr et al, 2002;Ligam et al, 2005;Blaschitz et al, 2011;Murthi et al, 2017;Wakx et al, 2018), yet the exact localization in the placenta remains contradictory (Sedlmayr et al, 2014). Contrary to other studies (Sedlmayr et al, 2002;Honig et al, 2004;Kudo et al, 2004), it has been recently observed that IDO1 is not expressed in villous or extravillous trophoblast and the increasing IDO activity at term is exclusively due to expression in endothelial cells (playing a role in immunosuppression and placental tone relaxation) (Blaschitz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The lowest AHR expression is reported in the brain, kidneys, and skeletal muscles [ 2 ]. Recent studies revealed additional functions of AhR in the body, including control of liver and vascular development, intestinal immunity, hematopoiesis, and perinatal growth [ 17 , 18 , 19 , 20 , 21 , 22 ]. Moreover, AhR signaling may be associated with stem cell proliferation and carcinogenesis [ 2 ].…”
Section: Aryl Hydrocarbon Receptor (Ahr)mentioning
confidence: 99%
“…AHR is abundantly expressed in the placenta to form a placental barrier between the mother and fetus [ 133 ]. Dioxins pass through the placenta and reach the fetus [ 134 , 135 , 136 ].…”
Section: Ahr and Clinical Symptoms In Yushomentioning
confidence: 99%